Performance of parallel plate-fin heat exchanger for piston aero-engines with front-placed guide plate at high altitude. (September 2022) - Liu, Zhentao; Sun, Meiyao; Huang, Yuqi; Li, Keyang; Li, Zhe; Gan, Binlin; Xiao, Maoyu
Highlights: Heat exchangers' performance in aircraft is enhanced by installing guide plates. New indicators relating thermal performance to structural parameters are proposed. The effect of inclination angle on thermodynamic performance is discussed. The shielding proportion would significantly affect the heat transfer capacity. Correlations are obtained to predict high-altitude characteristics. Abstract: The reduction in atmospheric density would hinder the normal operation of the cooling system of piston aero-engines, thus influencing the aircraft's performance in all aspects. This paper first introduced a composite structure consisting of a plate-fin heat exchanger and a front-placed guide plate to strengthen the heat transfer capacity. The improvement was evaluated and predicted by CFD (computational fluid dynamics) simulations at different altitudes. The optimal layout parameters of the guide plate, such as the inclination angle and the shielding proportion, were also explored. To scientifically elucidate the relationship between heat dissipation, flow performance, and structure parameters, the conception of effective mass rate was proposed for the first time. The results showed that the enhancement of the composite structure in heat transfer rate achieved a maximum improvement rate of 34.9% at 20 km altitude. Also, different arrangements of the guide plate directly affected the thermal and flow performance. Below 11 km, the best inclination angle of the plate was 30°, while above 11 km, it became 45°. The optimal gap in partial shielding cases decreased within 7∼9 mm as the altitude increased. Finally, relevant correlations for predicting the flow and heat transfer characteristics of the heat exchanger at different altitudes were developed in this study.